2014
DOI: 10.3171/2014.7.jns132793
|View full text |Cite
|
Sign up to set email alerts
|

Encephaloduroarteriosynangiosis for cerebral proliferative angiopathy with cerebral ischemia

Abstract: Cerebral proliferative angiopathy (CPA) is a rare clinical entity. This disorder is characterized by diffuse vascular abnormalities with intermingled normal brain parenchyma, and is differentiated from classic arteriovenous malformations. The management of CPA in patients presenting with nonhemorrhagic neurological deficits due to cerebral ischemia is challenging and controversial. The authors report a case of adult CPA with cerebral ischemia in which neurological deficits were improved after encephaloduroarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Clinical symptoms of CPA are seizures (45% patients), headaches (41%), focal neurological deficits (FNDs) not because of hemorrhage (16%), and cerebral hemorrhages (12%). Although it is rare that the onset of CPA is hemorrhagic, the chance of re-bleeding may be higher than in patients with typical AVMs [1,2] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical symptoms of CPA are seizures (45% patients), headaches (41%), focal neurological deficits (FNDs) not because of hemorrhage (16%), and cerebral hemorrhages (12%). Although it is rare that the onset of CPA is hemorrhagic, the chance of re-bleeding may be higher than in patients with typical AVMs [1,2] .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, increased regional cerebral blood flow perfusion may relieve clinical symptoms and improve prognosis of patient with CPA. Surgical procedures for treating moyamoya disease which can increase regional cortex's cerebral blood flow perfusion may benefit patients with CPA, Kono et al [2]. reported a case of adult CPA with cerebral ischemia in which neurological deficits were improved after encephaloduroarteriosynangiosis (EDAS).…”
Section: Treatmentmentioning
confidence: 99%
“…The clinical course is believed to be less aggressive than true AVMs. Symptoms usually relapse and remit over a few years, and might culminate with a more severe disturbance that motivates an emergency investigation or progresses to significantly impair the patients's quality of life (4,8,18) . However, Marks et al, 2011 (4) , reported a more rapid progression.…”
Section: Clinical Coursementioning
confidence: 99%
“…Perfusion images may play a role in the diagnosis and follow-up of these patients, to assess the extension of ischemic compromise and the efficacy of treatments (3,20) . Several methods were used across case reports and series, such as perfusion-weighted MRI (PW-MRI) (3,6,15,(20)(21)(22) , 123I-IMP-SPECT (21) , 99mTc-ECD-SPECT (18) , Positron Emission Tomography (PET) (23) , and 11C-METH PET (24) .…”
Section: Diagnosismentioning
confidence: 99%
“…Patients with CPA, typically young females, usually present with headaches, seizures, and progressive neurological deficits due to ischemia with vascular steal [4,5] . These patients have lower risk of hemorrhagic events than those with brain AVMs [1,4,6] .…”
Section: Cerebral Proliferative Angiopathy In a Childmentioning
confidence: 99%